Determinants of capital structure - An empirical investigation on Malaysian property PLCs - Ahmad, Norafifah; Ismail, Aniz (2012)
This study examines the impact of sub-mortgage loan crisis on the capital structure of eighty (80) publicly-listed Malaysian property firms during 2007-2009 in establishing which theory, Trade-off Theory (TOT) or Pecking Order Theory (POT) that explains the financing behavior adopted by the firms during the financial crisis.The capital structure determinants tested are firm size (SIZE), profitability (PROF), tangibility (TANG), non-debt tax shields (NDTS), growth opportunities (GROWTH), liquidity (LIQ), business risk (BR) and effective tax rate (ETR). The proxy for capital structure is long-term debt ratio (LTDR). Findings indicate that SIZE, PROF, TANG, NDTS and GROWTH affect LTDR positively.LTDR has positive and statistically significant correlations with size and profitability, but a negative and statistically significant correlation with LIQ. BR and ETR have negative relationships with LTDR.Our findings are inconsistent with almost all previous studies of TOT on the effect of PROF on LTDR, and of POT on GROWTH and ETR effects on capital structure.One distinct observation of our result is that PROF is able to explain the POT.The submortgage loan crisis clearly had affected the capital structure of the property sector through the decline of the debt levels of these firms. Finally, the results suggest that both theories (TOT and POT) explain the financing behavior of the sampled property firms, though, when taking into account the decline in the debt levels, POT seems to explain the financing behavior of the tested firms better than TOT.